2013
DOI: 10.1111/1574-6968.12216
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the spinach (Spinacia oleracea) spermosphere and phyllosphere bacterial communities

Abstract: The bacterial diversity of seeds, transmission of bacteria from seed to phyllosphere, and fate of seed-transmitted bacteria on mature plants are poorly characterized. Understanding the dynamics of microbial communities is important for finding bio-control or mitigation strategies for human and plant pathogens. Bacterial populations colonizing spermosphere and phyllosphere of spinach (Spinacia oleracea) seedlings and plants were characterized using pyrosequencing of 16S rRNA gene amplicons. Spinach seed microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 56 publications
(73 reference statements)
7
70
2
Order By: Relevance
“…For instance, in order to decrease the false-assignation rate of index reads in MiSeq experiments, we have considered only aOTUs in our analysis. Despite discrepancies between different studies, the range of bacterial richness observed in our study seems to be in accordance with previous results obtained on Brassica, Spinacia oleracea, and Triticum seeds (16,18). In addition, it is tempting to conclude that the seed microbiota contains on average fewer bacterial and fungal taxa than the microbial community associated with the rhizosphere (1, 60, 61) and a comparable level of diversity in comparison to the phyllosphere (2,61).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, in order to decrease the false-assignation rate of index reads in MiSeq experiments, we have considered only aOTUs in our analysis. Despite discrepancies between different studies, the range of bacterial richness observed in our study seems to be in accordance with previous results obtained on Brassica, Spinacia oleracea, and Triticum seeds (16,18). In addition, it is tempting to conclude that the seed microbiota contains on average fewer bacterial and fungal taxa than the microbial community associated with the rhizosphere (1, 60, 61) and a comparable level of diversity in comparison to the phyllosphere (2,61).…”
Section: Discussionsupporting
confidence: 90%
“…While the transmission of microorganisms from seed to seedling is the primary source of inoculum for the plant, relatively few research groups have investigated the composition of the seed microbiota (12)(13)(14)(15) and its dynamics during germination and emergence (16,17). Pioneer studies have highlighted (i) that the endophytic bacterial communities are relatively well conserved from one generation to another (15) and (ii) that germinating seeds are mostly colonized by soil microorganisms (13,17).…”
mentioning
confidence: 99%
“…Similar to studies of other edible green vegetables, we found that the majority of bacteria on our leaf samples could be assigned to Pseudomonadales and Enterobacteriales (27,45,46). Although Methylobacterium spp.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the short period of stress application (2 days in this study) might not have significant effects on bacterial counts, which are known to change over the long growing season (65,66). On the other hand, the structure of phyllosphere bacterial communities can be influenced by a number of environmental factors (63,67,68), which may explain the various significant correlations between the different viruses and the bacterial counts on lettuce and spinach observed under different conditions. In our study, both the levels of bacteria and the virus infectivity and RNA titers showed significant positive correlations under multiple conditions for multiple viruses.…”
Section: Discussionmentioning
confidence: 83%